2022
DOI: 10.3390/nu14030688
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Postnatal Choline Supplementation in Fetal Alcohol Spectrum Disorder

Abstract: Fetal alcohol spectrum disorder (FASD) is common and represents a significant public health burden, yet very few interventions have been tested in FASD. Cognitive deficits are core features of FASD, ranging from broad intellectual impairment to selective problems in attention, executive functioning, memory, visual–perceptual/motor skills, social cognition, and academics. One potential intervention for the cognitive impairments associated with FASD is the essential nutrient choline, which is known to have numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 189 publications
1
17
0
Order By: Relevance
“…Currently, choline supplementation is being investigated as an intervention to help reduce the severity of FASD [ 21 ]. Many clinical studies have examined the beneficial effects of both prenatal and postnatal choline supplementation on neurobehavioral and cognitive function in children with FASD [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, choline supplementation is being investigated as an intervention to help reduce the severity of FASD [ 21 ]. Many clinical studies have examined the beneficial effects of both prenatal and postnatal choline supplementation on neurobehavioral and cognitive function in children with FASD [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of treatments that reduce the severity of FASD is critical, specifically regarding interventions that can improve neurodevelopment and cognitive function. One potential intervention that is currently being investigated in FASD is the essential nutrient choline [ 21 ]. Choline is critical for normal brain development and cognitive function, with studies showing life-long memory enhancement in typically developing subjects that received perinatal choline supplementation [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interventions that include exercise and/or environmental enrichment [ 9 , 54 , 55 , 56 , 57 , 58 , 59 ], antioxidant supplementation [ 10 , 11 , 60 ], and other pharmaceutical therapies [ 61 ] have all shown some efficacy in mitigating ethanol’s effects. However, recent studies have demonstrated beneficial effects of the nutrient choline [ 29 , 62 ], and choline supplementation is emerging as one of the most promising treatments for FASD [ 32 , 62 ]. The present data illustrate that choline can mitigate the effects of PNEE on alterations in hippocampal plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional interventions, such as choline supplementation, show promise for promoting neurodevelopment in infants and children with PAE [ 90 , 91 , 92 ]. This opens the question of whether iron supplementation may be a viable intervention for individuals with PAE.…”
Section: Discussionmentioning
confidence: 99%